Pharmacological correction of the activity of bone remodelling markers in the oral fluid of patients with generalised periodontitis depending on blood type - Yurii Bandrivsky; Andrii Bambuliak; Orysia Bandrivska; Iryna Maika; Khrystyna Dutko; Lesia Kuchyrka (Pensoft Publishers, 2024)
This article presents the data on the effectiveness of the treatment complex we developed on the activity of bone remodelling markers in the oral fluid during the treatment of generalized periodontitis, depending on the blood group. The use of our proposed drugs of general and local action in patients with generalized periodontitis of different blood groups allowed to reduce the average content of TRACP in the oral fluid by 18.25%, while increasing the level of BSALP by 27.64% in comparison with the corresponding data before treatment, p, р1<0.05, 0.01, which indicates the predominance of bone remodelling processes over osteoresorption processes in patients of the main group. The tactics of treatment of patients with generalized periodontitis of different blood groups, which we propose, is more effective than the conventional therapy and contributes to a faster achievement of remission of generalized periodontitis.